2007
DOI: 10.1063/1.2736083
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of flow over traveling wavy foils in a side-by-side arrangement

Abstract: Flow over traveling wavy foils in a side-by-side arrangement has been numerically investigated using the space-time finite element method to solve the two-dimensional incompressible Navier-Stokes equations. The midline of each foil undergoes lateral motion in the form of a streamwise traveling wave, which is similar to the backbone undulation of swimming fish. Based on the phase difference between the adjacent undulating foils, two typical cases, i.e., in-phase and anti-phase traveling wavy movements, are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
107
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(121 citation statements)
references
References 45 publications
13
107
1
Order By: Relevance
“…This is very different from the model used in some previous works [11,12,14], where the body was held fixed in an oncoming flow. Although a single actively flapping body in self-propulsion has been studied before [17][18][19][20][21], the multibody interactions under such condition have never been considered.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…This is very different from the model used in some previous works [11,12,14], where the body was held fixed in an oncoming flow. Although a single actively flapping body in self-propulsion has been studied before [17][18][19][20][21], the multibody interactions under such condition have never been considered.…”
mentioning
confidence: 84%
“…Although numerous studies on fish schools [7], bird flocks [8], and systems containing bacteria or active particles [9,10] can be found in the literature, the mechanism by which stable aggregations are formed remains unclear. The hydrodynamic characteristics of two coupled flapping (or traveling wavy) foils have been studied in some previous works [11][12][13]. For fish schools, Weihs predicted that a diamondlike configuration of the positions of individuals is energetically optimal [14].…”
mentioning
confidence: 99%
“…Although Eqs. (2a) and (2d) have already been used by Dong (13) and Akimoto (10) , respectively, the other two amplitude Eqs.…”
Section: Basic Equations and Numerical Methodsmentioning
confidence: 99%
“…For example, in two-dimensions, Akimoto and Miyata (10) , Nakaoka et al (11) , and Sheu and Chen (12) have simulated flow fields induced by a deforming fish-like body placed in a uniform viscous flow using moving grid system such as arbitrary Lagrangian-Eulerian (ALE) approaches. Dong and Lu (13) have studied a side-by-side arrangement of fish and…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al studied the oscillation behaviour of a flexible plate in the wake of a D-section cylinder and found that the incoming vortices make the plate oscillate with large amplitude at the beginning and then slant laterally [18]. Dong [19], Zhang [20] and Wu [21] et al adopted CFD to illustrate the interactions between fish while cruising in groups and revealed their abilities to control vortices. Wang [22] and Alben [23][24][25] numerically analysed the influence of phase relationships between the flexible plate and the vortex on its force generation.…”
Section: Introductionmentioning
confidence: 99%